Pathology of striped dolphins (Stenella coeruleoalba) infected with Brucella ceti - González-Barrientos, Rocio (2009)
Seventeen striped dolphins (Stenella coeruleoalba) displaying swimming disorders compatible with neurological syndromes were investigated for Brucella infection. Sixteen dolphins had meningoencephalomyelitis. Serum antibody against Brucella antigen was detected in all 14 animals tested and Brucella ceti was isolated from eight out of nine animals. Brucella antigen was detected in the brain by immunofluorescence, but not by immunohistochemical labelling. By contrast, Brucella antigen was demonstrated by immunohistochemistry in the trophoblast of animals with severe placentitis and in the mitral valve of animals with myocarditis. The microscopical lesions observed in the tissues of the infected dolphins were similar to those of chronic brucellosis in man. The severity of brucellosis in S. coeruleoalba indicates that this dolphin species is highly susceptible to infection by B. ceti.